Genderové inovace v malém podnikání. Institucionální podmínky a dosahování genderové (ne)rovnosti u podnikatelských párů - Marie Dlouhá; Nancy Jurik; Alena Křížková (Gender a Výzkum, 2014)
Using the so-called embeddedness perspective, this article highlights the importance of context (time, space and institutions) for the direction of current research on the gender structure of entrepreneurship. The authors focus mainly on the effects of institutional context, namely tax and family policies, on business couples (copreneurs). The emphasis is on how these factors and formal institutions, which are reflected in informal gender norms, influence the work-life balance strategies of copreneurs. Based on a qualitative analysis of 24 in-depth interviews, the authors identify three strategies of achieving work-life balance and using welfare state measures: individualistic, adapting and innovating. Based on separate in-depth interviews with these business and life partners, we are also able to analyse the dynamics of communication between them. We draw attention to the finding that the strategies identified are not exclusive and may change during one’s life course and business career. Despite their differences, in some respects all these strategies preserve and reproduce gender inequality because it is embedded in the social context and institutional framework for economic activity and work-life balance in the Czech Republic.